2020
DOI: 10.1097/md.0000000000021146
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian metastasis in women with cervical carcinoma in stages IA to IIB

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 29 publications
(60 reference statements)
0
25
0
1
Order By: Relevance
“…Tumor histology has been identified as an important factor in predicting rate of ovarian metastasis, with many studies supporting lower rates with squamous cell carcinomas compared with adenocarcinomas 4–9. Yamamoto and colleagues reviewed the surgical specimens of a large cohort of 255 patients with cervical cancer and reported a 0.4% risk of ovarian metastasis with squamous cell carcinomas compared with an 8.2% risk in non-squamous tumors 4.…”
Section: Patient Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tumor histology has been identified as an important factor in predicting rate of ovarian metastasis, with many studies supporting lower rates with squamous cell carcinomas compared with adenocarcinomas 4–9. Yamamoto and colleagues reviewed the surgical specimens of a large cohort of 255 patients with cervical cancer and reported a 0.4% risk of ovarian metastasis with squamous cell carcinomas compared with an 8.2% risk in non-squamous tumors 4.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Recently, Fan and colleagues conducted a meta-analysis that included 12 studies of patients with IA-IIB disease and reported on ovarian metastasis rates. They found that while adenocarcinoma recurrence risk was significantly higher (OR 3.89, 95% CI 2.62 to 5.78), overall rates were low for both adenocarcinomas (3.61%) and squamous carcinoma histologies (1.46%) 7. Transposition may therefore be approached with caution and other risk factors in early-stage squamous cell carcinomas and adenocarcinomas of the cervix should be considered 7 11…”
Section: Patient Selectionmentioning
confidence: 99%
See 3 more Smart Citations